Return and Dynamics: The Path of Labor Migration when Workers Differ in their Skills and Information Is Asymmetric - Oded Stark (The Scandinavian Journal of Economics, 1995)
An implementation of the theory of labor migration under asymmetric information shows that return migration arises from the reinstatement of informational symmetry which induces low-skill workers, who are no longer pooled with high-skill workers, to return. When workers in an occupation constitute more than two skill levels, say four (without loss of generality), the following patterns emerge: Migration is sequential, that is, it proceeds in waves. Each wave breaks into workers who return and workers who stay; within waves the returning migrants are the low-skill workers. The average skill level of migrants is rising in the order of their wave.
Keywords: 330